Pycnogenol® French maritime pine bark extract in randomized, double-blind, placebo-controlled human clinical studies - Weichmann, Franziska; Rohdewald, Peter (Frontiers in Nutrition, 2024)
Pycnogenol ® French maritime pine bark extract is a well-known and thoroughly studied patented extract from the bark of Pinus pinaster Ait. ssp. Atlantica. In 39 randomized double-blind, placebo-controlled (RDP) human clinical trials including 2009 subjects, Pycnogenol ® French maritime pine bark extract supplementation for two weeks to six months has been shown to beneficially affect cardiovascular health, chronic venous insufficiency, cognition, joint health, skin health, eye health, women's health, respiratory health and allergies, oral health and sports performance. The mechanisms of action that can explain the respective effects on different conditions in the human body are discussed as well. As investigated in several in vitro, in vivo and in clinical studies, Pycnogenol ® French maritime pine bark extract showed antioxidative effects, antiinflammatory abilities, beneficial effect on endothelial function and reinforcing effects on the extracellular matrix. The present review aims to give a comprehensive overview of currently available "gold standard" RDP trials of Pycnogenol ® 's benefits across various health domains compared to placebo. In addition, some of the processes on which the presented effects of Pycnogenol ® French maritime pine bark extract are based will be elucidated and discussed. This broad overview of RDP studies on Pycnogenol ® in different health domains can be used as a basis for further research on applications and mechanisms of this unique French maritime pine bark extract.